Population dynamics of endangered blanding's turtles in a restored area. Issue 3 (17th December 2015) - Reid, Brendan N.; Thiel, Richard P.; Peery, M. Zachariah
ABSTRACT: Habitat protection and restoration are used to promote recovery in endangered reptile species, yet the long‐term consequences of these efforts can be difficult to assess. Measuring the effects of habitat restoration on turtles can be especially difficult because of long generation times and consequent time lags between restoration activities and population‐level responses to these activities. We collected 24 years of mark‐recapture, size structure, and nest survival data on a population of International Union for Conservation of Nature (IUCN)‐Endangered Blanding's turtles ( Emydoidea blandingii ) inhabiting a large restored wetland‐upland complex in Wisconsin, USA. We used these data to examine survival and recruitment in the population and the response of individual aggregations of nesting females to recent restoration of an extensive upland prairie‐oak barrens nesting habitat. The population exhibited positive growth over the 24‐year period (λ   = 1.03) based on temporal asymmetry mark‐recapture models. Population growth rates were greatest in a recently restored prairie‐barrens nesting area because of relatively high recruitment of nesting females. Females nesting in the recently restored prairie‐barrens habitat were smaller and decreased in size over time compared to females using 2 older nesting areas, suggesting that recruitment was relatively high because of an influx of young breeding females. Nest depredation probability decreased with increasing distance from forest edges, suggesting that the recent clearing of woody vegetation in recently restored habitat increased reproductive success. Collectively, our results highlight the potential benefits of habitat restoration to turtles and identify upland habitats as a key to promoting population growth in turtles with complex habitat requirements. © 2015 The Wildlife Society.